Tantangan Etika Dalam Globalisasi Ekonomi: Perspektif Keadilan Sosial - Juan Sibarani; Tri Kurnia; Bonaraja Purba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ethics and moral values, direct people and societies in controlling their behavior. In other words, this definition is also known as a set of values that guide human actions both as individuals and societies. Today, there are many ethical issues that need to be addressed in light of the rapidly growing global economy. The purpose of this study is to Implementation of ethics in the era of globalization is necessary, because the lifestyle of people in the global era has changed, the exposure to communication in the global era has a very broad influence, globalization can threaten the fading of the community value system in all aspects of life the growing globalization of the economy provides access to a very large market for businesses. As a result, market players compete fiercely to outperform each other. The process of globalization has also resulted in the blurring of business boundaries between countries as each country's economy integrates into the world economy. Economic inequality, both within and between countries, is increasing, and this raises ethical questions in the era of globalization. Growing economic inequality is a result of globalization, with a few people and multinational corporations reaping huge profits at the expense of the vast majority. The environment is often negatively impacted by economic globalization. To maximize profits, multinational corporations often exploit natural resources.